Ileocolonic neuroendocrine tumours identified in the English bowel cancer screening programme. (2nd April 2018) - Basuroy, R.; O'Donnell, C. M.; Srirajaskanthan, R.; Ramage, J. K.
Abstract: Aim: Ileocolonic neuroendocrine tumours (NETs) are diagnosed as part of bowel cancer screening programmes (BCSPs). The aim of this study was to identify and characterize NETs diagnosed within the English BCSP, a double‐screen programme that uses guaic faecal occult blood test (gFOBT) screening and colonoscopy, by interrogating the national colorectal screening database and validating the findings with individual BCSP centres. Method: The Exeter database was interrogated by running queries to identify participants with coded NETs (from the start of the programme in July 2006 – 1 December 2014). A written proforma was sent to the responsible BCSP clinician for validation and characterization. Results: During this period, 13 061 716 participants were adequately screened using gFOBTs, and 259 765 participants had definitively abnormal results. There were 146 unique participants with NET‐related codes from 216 707 BCSP colonoscopies. The diagnosis rates per 100 000 colonoscopies were 29 rectal, 18 colonic and 11 ileal NETs. The majority of rectal NETs had Grade 1 (80%) and Stage T1 (85.1%) disease. Over half of ileal NETs (53.6%) in this study had invasive disease, with 85.2% having nodal and 36.1% having metastastatic disease. Conclusion: The current study highlights the rate of colorectal NETs diagnosed in the English BCSP. These data highlight a higher‐than‐anticipated incidence, and the potential additional benefit of BCSPs in identifying occult NETs.